(3GdYhGed GdeDKQI Ydi JLGQH GdTQcGJ GdeUQjI GdfGLMI ai YedjI GdJOhjd (B: s (3OQGSI JWHjbjI (B= Factors influencing the experiences of successful Egyptian companies in the process of internationalization , An emperical study / s - (3ESdGe YHOGdSdGe YHOGdNGdb SdGegs; (3CTQa EeGe eUWai (B: s; (3YHOGdMejO eUWai CHh fGYe (B: s ((3GdbGgQI (B: s (3ESdGe YHOGdSdGe YHOGdNGdb SdGeg (B: s, 2017)
(3JgOa gPg GdOQGSI Gdi GSJcTGa GdYhGed GdeDKQI Ydi JLGQH GdTQcGJ GdeUQjI GdfGLMI ai YedjI GdJOhjd(B: (3h GdCSFdI GdHMKjI GdQFjSjI dgPg GdOQGSI gi(B: (3cja bGeJ GdTQcGJ GdeUQjI GdfGLMI HJOhjd GfTWJgG ai GdbWGY GdUfGYi?(B. (3HGdEVGaI Gdi Cge GdYhGed GdJi CKQJ Ydi YedjI JOhjd GdCfTWI ai GdbWGY GdUfGYi GdeUQi?(B. (3I Edi GdELGHI Yf gPg GdCSFdI GJHY GdHGMK GdefgL GdfhYi Yf WQjb GdebGHdGJ GdTNUjI THg GdgjcdjI eY eOjQi h eSFhdi GdJUOjQ ai GdTQcGJ GdeUQjI GdJi Jbhe HCfTWI OhdjI h Ydi GdCbd GdJUOjQ(B. (3h bO NdUJ GdOQGSI Gdi Gf gfGc GQHYI YhGed QFjSjI JDKQ Ydi YedjI GdJOhjd HGdfSHI ddTQcGJ GdeUQjI h gi(B: (3YhGed NGUI HGdTQcI(B: (3h YhGed NGUI HJhLgGJ QhGO GdCYeGd(B: (3h YhGed NGUI HHjFI GdTQcI(B: (3h YhGed NGUI dGYdGbGJ GdTHcjI GdJi chfJgG GdTQcI CKfGA YedjI GdJOhjd(B. (3h Gf GcKQ gPg GdYhGed JCKjQG ai GdHjFI GdeUQjI geG(B: (3GdYhGed GdNGUI HHjFI GdTQcI(B: (3h cPdc GdYdGbGJ GdTHcjI ddTQcIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJLGQI (B- (3bSe EOGQI GdCYeGds
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJOhjds; (3GdTQcGJ GdeUQjI s; (3GdbWGY GdUfGYis